Tradisi Selawat Burdah Ijazah K.H. Wahab Chasbullah di Kalangan Santri Bahrul Ulum Tambakberas Jombang Jawa Timur (1965-1971) - Tis'atul Fitriyani; Nur Mukhlis Zakariya (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2022)
This study aims to analyze the existence of a traditionalist culture, namely the tradition of reading selawat burdah among the students of the Bahrul Ulum Islamic Boarding School, Tambakberas, Jombang, East Java. Usually, a traditional culture will gradually die because it is eroded and attacked by the currents of modernization and globalization today. However, this does not apply to the tradition of reciting Burdah's selawat at the Bahrul Ulum Islamic Boarding School, Tambakberas, Jombang, and instead continues to exist and be sustainable. It is this phenomenon that researchers have studied using historical research methods with a cultural anthropological approach. Then the analysis researchers used Soekanto's role theory. The results of this study revealed that the tradition of reciting the Burdah selawat at the Bahrul Ulum Islamic Boarding School, Tambakberas, Jombang was brought by K.H. Wahab Chasbullah which was later awarded to K.H Jamaluddin Ahmad. The role of K.H Chasbullah and his charismatic figure became a key factor in the preservation of this tradition among his students. The sustainability of this tradition is also strengthened by the belief of the community and among the students of Bahrul Ulum, Tambakberas, Jombang, that the Burdah salawat has supernatural powers that contain many benefits for life. Another implication of this tradition is that it is also a means of proselytizing the spread of Islam through art because it gave birth to the Al-Banjari selawat music group which is popular with the public.